PEMURNIAN MINYAK GORENG DARI BIJI KARET (Havea brasiliensisRoxb.,)MENGGUNAKAN ZEOLIT - Arya Setiawan; Usman Pato; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rubber is one of the agricultural commodities that are abundant in Indonesia. One alternative to utilizethe rubber seed is using it’s oil as cooking oil. The oils must be purified by adsorption process using zeolite. This is because rubber seed oil can not be consumed directly due to high toxiccyanide compound. The aim of this study was to obtain quality cooking oil from rubber seed in accordance with quality standard of cooking oil and a low cyanide acid content. This study was conducted experimentally by using Completely Randomized Design (CRD) with 4 treatments, namely Z1 (25% zeolite with long adsorption 8 hours), Z2 (25% zeolite with long adsorption 10 hours), Z3 (25% zeolite with long adsorption 12 hours) and Z4 (25% zeolite adsorption time 14 hours) with 4 replications. Data obtained were analyzed statistically using Analysis of Variance (ANOVA) and if F count is greater than or equal to F table then continued with DNMRT test at 5% level. The results show that the longer the time of adsorption in the refining rubber seed oil significantly decreased the contents of cyanide and acid number as well as density but increased saponification. It can be concluded that the best treatment was Z4 treatment (25% zeolite for 14 hours adsorption) with the content of cyanide1,97 ppm, acid number 2,61 mgKOH/g, saponification 143,62 mgKOH/g and density 0,898 g/ml.   Keywords: Purification, rubber seed, cooking oil, zeoliteandadsorption.